IMPLEMENTASI GUIDED INQUIRY BERBANTUAN E-LKPD TERHADAP HASIL BELAJAR KOGNITIF SISWA PADA MATERI REDOKS DAN TATA NAMA SENYAWA KIMIA (Jurnal Inovasi Pendidikan Kimia, 2021)
Chemistry learning in schools tends not to provide a place for students to be active and does not train their minds to foster students' curiosity. The application of the guided inquiry learning model is learning that involves all students' abilities to find and investigate something so that it is in accordance with their experience. The guided inquiry model can be used to make it easier for students to understand concepts, especially in redox material and the nomenclature of chemical compounds. This study aims to determine student cognitive learning outcomes on redox material and chemical compound nomenclature through the guided inquiry model assisted by e-LKPD. The population used was science class X-4 to X-6 at a Kendal high school. The sampling technique was carried out by means of cluster random sampling. The sample was obtained after the population was tested for normality and homogeneity, so that the students of science class X-4 as the experimental class and X-5 as the control class. The research data was taken by the test method to determine the student's cognitive learning outcomes. The data analysis technique used to test the hypothesis is a biserial correlation technique. The results showed that there was a strong or high positive relationship based on the r value in the calculation, namely 0.60. This shows that there is an effect of guided inquiry learning assisted by e-LKPD on student cognitive learning outcomes, which is 36%.